MOBILE COMMMERCE PENJUALAN PADA TB. GALANG DI DESA NEGERI KATON - Kasmi Kasmi; Wahyu Triatmojo (STMIK Pringsewu, 2021)
TB. Galang is a building shop located in Katon Country which sells various building materials such as cement, ceramics, natural stone and other building tools. Sales and purchase transactions are still carried out using note paper, where the supply of goods in the sales transaction is still handwritten, so that errors can still occur in writing data, because it becomes inaccurate when goods come in, until the profit calculation is less efficient, when doing it. sales transactions. When making a more computerized sales transaction, an Information System design is built to make sales easier, and in the system it has a feature that can search for stock items, provision of goods in a report, profit, and sales transactions. This system uses the waterfall research method. The existence of this information system, everything can be done easily and goes well in making sales transactions. The existence of this system can increase the number of sales and make it easier to produce sales reports.